Financial systems development and local financial institutions in Indonesia: Introduction and selected bibliography - Detlev Holloh (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1996)
The interventionist rationale of economic policy-making in Indonesia was already laid down in the 1945 constitution, but only the abundant oil revenues during the oil boom period between 1973 and 1982 enabled the government to realize the envisaged state-led model of development. In order to channel revenues to domestic industries, state enterprises and cooperatives, the government strengthened the position of state banks vis-à-vis the private sector. By 1982, state banks accounted for 80% of total banks assets and 85% of total bank credit. The central bank established a system of 32 subsidized liquidity credit programs at controlled interest rates. More than 90% of liquidity credit, which made up almost half of the total loan amount disbursed during the oil boom period, were channeled through state banks. By 1982, small-scale credit accounted for almost one quarter of the total loan amount channeled through subsidized liquidity credit programs. The rural financial system was virtually closed for the private sector. Bank Rakyat Indonesia (BRI) was instructed to establish an extensive network of village units for the implementation of the subsidized credit programs.
Keywords: 330; Informeller Finanzsektor; Gemeinde; Indonesien